Extradition in Fascist Italy (1922-1943) and in Brazil of Getúlio Vargas (1930-1945) between the ascension of “Fascism Criminal Law” and the survival of the liberal tradition of Criminal Law - Nunes, Diego (Revista Seqüência: Estudos Jurídicos e Políticos, 2019)
This paper aims to present the legal treatment given to extradition in Fascist Italy and in the Brazil of Getúlio Vargas to understand if the institute has suffered authoritarian torsions both on the field of domestic Law and on the diplomatic relations between these countries. On the Codice Rocco, the provision on extradition was meant to strengthen the repression. On its turn, if on one side the 1938 Brazilian Extradition Act relies on the elements of the institute created in the nineteenth century, it also adds important elements to the defence of a strong State. However, the Italian-Brazilian extradition treaty of 1932 attached to the liberal paradigm ended up protecting the individuals subjected to extradition. Thus, were these rules truly of a fascist origin? The hypothesis is to realize that the “Fascism Criminal Law” is not quite a revolution, since despite introducing major changes it cohabits with the liberal tradition of Criminal Law.